Patient displays of stalking in mental health settings: staff member experiences, responses and burnout - Ward, Lauren (2020)
The study aimed to explore experiences mental health employees have of stalking by service users, the responses utilised to these incidents, and the impact this had on burnout. This research was justified by previous indications that stalking, and burnout are prevalent in mental health services. Previous research has advised that the effectiveness of stalking responses in these settings should be assessed. Stalking was was found to have separate positive correlations with burnout and emotional exhaustion, however, only the correlation with emotional exhaustion was significant. Moreover, while there was a difference in the relationship stalking had with burnout between the two responder groups, this interaction was not significant. This previously unexplored combination of concepts was valuable and recommendations for future research could be offered. The limited variance in burnout accounted for by stalking revealed that alternative precursors should be explored in future.